Identification of Neutralization of the CMR Documents in European Union Conditions - Milos Poliak; Jana Tomicova; Marek Jaskiewic; Pawel Drozdziel; Natalia Lakhmetkina (Communications - Scientific letters of the University of Zilina, 2020)
Year 1956 was an important year for international road and freight transport. By this year Convention on the Contract for the International Carriage of Goods by Road (CMR) was made. The basic purpose of the Convention was to unify the rules in the international carriage of goods and thereby promote development of international trade. From the practical point of view, this was very important for both carriers and transporters. This Convention also describes the most important document in the international carriage of goods, which includes the consignment note of CMR as well. Recently this document is often associated with the term neutralization. Objective of this article was to clarify the meaning of this phrase in transport. In addition, the aim was to find out in what range carriers have real experience with neutralization of the consignment note of the CMR during the transport, for what types of goods and on what types of routes is the neutralization being used the most.